Report of the virus discovery workshop held at the International Livestock Research Institute, Nairobi, 5-8 November 2012 - International Livestock Research Institute (2012)
The virus discovery workshop was held at the International Livestock Research Institute (ILRI) Nairobi from 5th to 8th November 2012. The workshop brought together scientists conducting research in the area of virus/pathogen discovery. The workshop aimed at enabling ILRI make informed decisions about which technologies to invest in to support the activities in the CGIAR Research Program on Agriculture for Improved Nutrition and Health (A4NH). The workshop was supported by A4NH with partial input from Roche Applied Sciences.